2015
DOI: 10.1002/chem.201502772
|View full text |Cite
|
Sign up to set email alerts
|

Bifacial Base‐Pairing Behaviors of 5‐Hydroxyuracil DNA Bases through Hydrogen Bonding and Metal Coordination

Abstract: A novel bifacial ligand-bearing nucleobase, 5-hydroxyuracil (U(OH) ), which forms both a hydrogen-bonded base pair (U(OH) -A) and a metal-mediated base pair (U(OH) -M-U(OH) ) has been developed. The U(OH) -M-U(OH) base pairs were quantitatively formed in the presence of lanthanide ions such as Gd(III) when U(OH) -U(OH) pairs were consecutively incorporated into DNA duplexes. This result established metal-assisted duplex stabilization as well as DNA-templated assembly of lanthanide ions. Notably, a duplex posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 45 publications
3
40
0
4
Order By: Relevance
“…Our previous study revealed that most of the lanthanide ions and Zn(II) ions affected the thermal stability of the U OH -containing DNA duplexes [31]. Based on the results, Gd(III) and Zn(II) ions were chosen to investigate the pH dependence of metal complexation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that most of the lanthanide ions and Zn(II) ions affected the thermal stability of the U OH -containing DNA duplexes [31]. Based on the results, Gd(III) and Zn(II) ions were chosen to investigate the pH dependence of metal complexation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as it is well known that the U OH base forms a Watson-Crick-type hydrogenbonded base pair with adenine nucleobase (U OH -A) [32][33][34][35], it therefore shows bifacial base pairing behaviors. The U OH -Gd(III)-U OH base paring thermally stabilized the DNA duplexes, while addition of Gd(III) ions to the U OH -A base pairs caused a duplex destabilization [31]. Metal complexation of the U OH bases accompanied the deprotonation of the 5-OH group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 The carbonyl oxygen atom and the 5-hydroxy group offer a bidentate metal coordination site for metalmediated base pairing. Figure 10 for clarity).…”
Section: Lanthanide-mediated Base Pairingmentioning
confidence: 99%
“…Schematic representation of bifacial base pairing behaviors of U OH nucleobases, which form both metal-mediated U OH Gd III U OH base pairs and hydrogen-bonded U OH A base pairs. 70 Other possible coordinating ligands on the Gd 3+ ions are not shown for clarity. incorporated a dATP 107 or a dTTP 108 opposite a template C possibly through the formation of Ag(I)-mediated AAg I C or TAg I C base pairs (Figures 11b and 11c).…”
Section: Recent Applications Of Metallo-base Pairsmentioning
confidence: 99%